The Impact of Phosphorus on Plant Immunity. (5th January 2021) - Chan, Ching; Liao, Ya-Yun; Chiou, Tzyy-Jen
Abstract: Phosphorus (P) is the second most essential macronutrient in terms of limiting plant growth. The genes involved in P acquisition, transport, storage, utilization and respective regulation have been extensively studied. In addition, significant attention has been given to the crosstalk between P and other environmental stresses. In this review, we summarize recent discoveries pertaining to the emerging function of P in plant immunity. The roles of external soil P availability, internal cellular P in plants, P starvation signaling machinery and phosphate transporters in biotic interactions are discussed. We also highlight the impact of several phytohormones on the signaling convergence between cellular P and immune responses. This information may serve as a foundation for dissecting the molecular interaction between nutrient responses and plant immunity.